PTU-020 Rifaxamin is a highly efficacious treatment for the parkinsonian phenotype of hepatic encephalopathy (HE). (28th May 2012) - Kok, B; McPhail, M; Foxton, M; Shawcross, D
Abstract : Introduction: Patients who develop Parkinsonian symptoms on a background of cirrhosis and portosystemic shunting (PSS) form a unique subset of so-called acquired hepatocerebral degeneration. The syndrome is entirely different from acute HE and other forms of Parkinsonism that develop in patients without liver disease and rarely responds to standard treatments for HE. Rifaxamin is a non-absorbable antibiotic which has recently been shown to be efficacious in the secondary prevention of recurrent HE and is postulated to decrease gut ammonia production and/or bacterial translocation. Methods: To prospectively evaluate the efficacy of rifaxamin 600 mg twice daily in three patients referred to the HE clinic at our institution with advanced cirrhosis, evidence of PSS and debilitating HE with extrapyramidal symptoms including resting tremor, bradykinesia, cog-wheel rigidity, drooling, loss of facial expression, shuffling gait and excessive somnolence. Each patient was evaluated independently by a hepatologist and a neurologist. Neuropsychological function testing (Trails A and B test), random venous ammonia (NH3 ), EEG and MRI brain/DaTscan were performed pre- and 4 weeks post rifaxamin. Results: Patient 1 [male, age 61, α1AT, NH3 76 μmol/l] was unable to complete Trails A/B test at baseline. On rifaxamin his severe bradykinetic rigidity syndrome, drooling and leaning to one side on walking resolved. His repeat Trails B test was in 75–90 th centile for a normal healthy age-matched population. His symptoms improved further on long acting dopamine therapy. Patient 2 [female, age 64, alcohol, abstinent, NH3 67 μmol/l] had an improved Trails A from the 10 th to 50 th centile, with resolution of bradykinesia, resting tremor and a dramatic reduction in her somnolence. Patient 3 [male, age 66, alcohol, abstinent, NH3 67 μmol/l] had remarkable improvement in his asymmetric bradykinetic rigid syndrome, regained his facial expression and was mobile with assistance whereas previously he had required hoisting. None of the patients had any improvement in their ammonia level or EEG with rifaximin despite resolution of symptoms. In the first two patients MRI brain post rifaxamin showed no change (high T1 signal in the globus pallidus) and in patient 3 a DaTscan post rifaxamin still showed decreased uptake in the right corpus striatum, in spite of dramatic clinical improvements. Patient 1 has now been transplanted and his extrapyramidal and neurocognitive symptoms have now resolved suggesting that this extrapyramidal syndrome is reversible. Conclusion: Rifaxamin is efficacious in the treatment of the Parkinsonian phenotype of HE in this small case series which appears to be independent of ammonia lowering. Larger clinical trials are now warranted. Competing interests: None declared.